Pengembangan E-Government Sebagai Langkah Mewujudkan Smart Government Di Kota Padang Panjang - Fahdea Medina Maharani; Roni Ekha Putera; Ria Ariany (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2023)
This study aims to analyze the development of e-government as a step towards creating smart government in the city of Padang Panjang. E-government development is useful for realizing maximum public services and effective and efficient performance management through the use of information and communication technology. According to Harvard JFK School of Government, e-government development takes into account three important elements, namely: support, capacity, and value. The research method used is qualitative with observation data collection techniques, interviews, and documentation. The results showed that various forms of innovation e-government as a step towards creating smart government in the city of Padang Panjang through the Padang Panjang Communication and Information Office in collaboration with several related OPD. However, in the implementation process there are still obstacles in the form of information and communication technology infrastructure, namely servers that sometimes have problems, this is part of the capacity element. Therefore, in the future the Municipal Government of Padang Panjang needs to be improved the quality of information and communication technology infrastructure procurement, especially about servers.